Millennial Experience in Islamic Banking: A Comparative Study between Clients and non-Clients - Ferty Nadya Pujianti; Phuc Thi Hanh Tran; Ira Novianty (Politeknik Negeri Bandung, 2021)
This study examines factors affecting millennial loyalty to Islamic banks, from the perspective of both customers and non-customers. It employed the quantitative method and was assessed with an exploratory-descriptive approach. The study was conducted in Bandung by distributing questionnaires to 200 non-customers and 200 customers of Islamic banks who were between 19-39 years old. Partial Least Square analysis was employed to evaluate the data. The results show that the exploratory-descriptive approach is able to provide complete information about the customer and non-customer loyalty toward Islamic banks. This research underlines that service quality is a significant factor in building customer loyalty while opinion leader is an influencing factor for non-customer loyalty. The study, then, provides guidelines for banking management to improve service quality and to develop marketing strategies using opinion leaders. Besides, it is also advisable for the managers to adjust themselves to the latest trends and millennials lifestyles.